Outpatient-Polyclinic Register of the Multidisciplinary Medical Center (TERRA): general characteristics and first results - M. M. Lukyanov; E. Yu. Andreenko; A. A. Smirnov; M. M. Kudryavtseva; N. N. Kuzina; V. G. Klyashtorny; R. N. Shepel; L. N. Ryzhakova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To describe the experience of creating the Outpatient-Polyclinic Register of the Multi-specialty Medical Center (TERRA) and the first results of the study.Material and methods. The TERRA registry included 32264 patients (age 44,0±15,3 years; 32,2% men) who applied to the multidisciplinary medical center from January 1, 2018 to December 31, 2021. Information from electronic outpatient records was evaluated. The data of patients with/without cardiovascular diseases (CVDs) in those who applied to general practitioners, cardiologists and other specialists, those with and without coronavirus disease 2019 (COVID-19) were compared.Results. There were 26,8% of patients with CVDs, while with ≥2 CVD — 8,1%, with CVD and/or chronic non-cardiac disease — 54,1%, their combination — 26%. Among those who consulted cardiologists, general practitioners and doctors of other specialties, hypertension was most often recorded — 64,8; 34,9 and 18,6%, coronary artery disease — 15,1, 6,2 and 3,2%, while from chronic non-cardiac diseases — diseases of the digestive system (64,4; 58,0 and 33,7%), kidneys (29,8; 24,9 and 13,2%), respiratory organs (28,4; 23,8 and 12,6%). The proportion of COVID-19 survivors was 8.2%, in patients with and without CVD — 14,8 and 5,1%, respectively (p<0,001). The proportion of CVD cases among survivors and non-survivors of COVID-19 was 58,0% and 25,2%, respectively (p<0,001). In addition, 88% of patients with CVDs consulted a cardiologist or general practitioner, of which 42% were observed by them together.Conclusion. The majority of patients at the multidisciplinary medical center had CVDs and chronic non-cardiac diseases, and more than a quarter had a combination of both. Patients with CVDs were more likely to have chronic non-cardiac diseases (2,2 times) and a history of COVID-19 (2,9 times). Among patients with a history of COVID-19, there was a higher proportion of cases of CVDs (by 2,3 times) and chronic non-cardiac pathology (by 1,8 times). Almost half of patients with CVD were observed jointly by a cardiologist and a general practitioner.